2020
DOI: 10.3390/ma13061325
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vanadate, Phosphate, Fluoride Compounds on the Aqueous Corrosion of Magnesium Alloy AZ31 in Dilute Chloride Solutions

Abstract: The anodic polarization response of magnesium alloy AZ31 was first characterized during exposure to aerated 0.1 M NaCl solutions with millimolar additions of NaVO3, Na3PO4, Na2HPO4, NaF and various pairings to assess their ability to inhibit corrosion kinetics and retard localized corrosion. Each of the candidate inhibitors reduced the corrosion rate of the alloy to some degree. A Na3PO4–NaVO3 pair produced a good inhibiting effect decreasing the corrosion rate to about 10−7 A/cm2, which was two orders of magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Exposure in a higher concentration (5 mM and 10 mM) versus a lower concentration (1 mM) resulted in an increment of 0.14 V of breakdown potential. The breakdown potential and the corrosion potential may be assessed as the resistance to localized corrosion, with larger values indicating a lower probability of localized corrosion during free corrosion exposures [ 15 ]. Therefore, the coating in a high selenite concentration bath benefited the resistance to localized corrosion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure in a higher concentration (5 mM and 10 mM) versus a lower concentration (1 mM) resulted in an increment of 0.14 V of breakdown potential. The breakdown potential and the corrosion potential may be assessed as the resistance to localized corrosion, with larger values indicating a lower probability of localized corrosion during free corrosion exposures [ 15 ]. Therefore, the coating in a high selenite concentration bath benefited the resistance to localized corrosion.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other conventional Mg coatings in a similar testing environment, the Se-based protective film has better performance than vanadate, stannate and Ce 3+ , has similar performance with PO 4 3− and Ca 2+ , and can be comparable to chromate [ 12 , 15 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 46 , 47 ]. Since the study of the selenite-based protective film was blank before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The external methods include surface treatment and coating processes (electroplating, chemical conversion coating, electrochemical conversion coating, laser/ion or electron beam treatment, sol-gel coating, and organic coating, etc.) [ 6 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Among them, the surface coating method may be the most simple and direct method.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] For example, Feng et al investigated the effect of the addition of NaVO 3 , Na 3 PO 4 , Na 2 HPO 4 , NaF, and various pairings of these inorganic salts on the polarization response of AZ31 exposed to 0.1 M NaCl solution, and the result suggested that all of these inorganic salts and their pairing reduced the corrosion rate of AZ31 except for NaF, in which the 10 mM Na 3 PO 4 -4 mM NaVO 3 inhibitor pair exhibited the best inhibition effect, decreasing the corrosion rate of AZ31 by nearly two orders. 29 Zhou et al suggested that the maximum inhibition efficiency of AZ31 in 3.5% NaCl reached 81.5% at a Na 3 PO 4 concentration of 1.0 g L À1 , while the Na 3 PO 4 concentration keeps on increasing; the inhibition efficiency decreases due to a remarkable shedding of the product layers. 30 For Mg-anode batteries, finding an electrolyte additive that not only activates the anode surface passivated layer but also reduce the self-corrosion rate of the Mg anode during the nodischarging periods is important.…”
Section: Introductionmentioning
confidence: 99%